'Balanced ischaemia' on ECG in dual territory STEMI. Issue 8 (9th August 2018) - Balakrishnan, Iswaree Devi; Chin, Chee Yang; Teo, Louis; Tan, Boon Yew; Yeo, Khung Keong
Abstract: Culprit lesion identification in ST elevation myocardial infarction (STEMI) is often guided by electrocardiogram (ECG) changes. However, in the setting of multi-vessel coronary artery occlusion, this can be challenging. We describe an interesting case of dual territory STEMI with unanticipated ECG changes that bring forth the concept of 'balanced ischaemia'. These seemingly bizarre findings are well explained using the fundamentals of electrocardiography reinstating its relevance in modern day cardiology.